Utilization of pain and sedation therapy on noninvasive mechanical ventilation in Korean intensive care units: a multi-center prospective observational study - Kim, Taehee; Kim, Jung Soo; Choi, Eun Young; Chang, Youjin; Choi, Won-Il; Hwang, Jae-Joon; Moon, Jae Young; Lee, Kwangha; Kim, Sei Won; Kang, Hyung Koo; Sim, Yun Su; Park, Tai Sun; et al. (Acute and critical care, 2020)
The use of sedative drugs may be an important therapeutic intervention during noninvasive ventilation (NIV) in intensive care units (ICUs). The purpose of this study was to assess the current application of analgosedation in NIV and its impact on clinical outcomes in Korean ICUs. Twenty Korean ICUs participated in the study, and data was collected on NIV use during the period between June 2017 and February 2018. Demographic data from all adult patients, NIV clinical parameters, and hospital mortality were included. A total of 155 patients treated with NIV in the ICUs were included, of whom 26 received pain and sedation therapy (sedation group) and 129 did not (control group). The primary cause of ICU admission was due to acute exacerbation of obstructed lung disease (45.7%) in the control group and pneumonia treatment (53.8%) in the sedation group. In addition, causes of NIV application included acute hypercapnic respiratory failure in the control group (62.8%) and post-extubation respiratory failure in the sedation group (57.7%). Arterial partial pressure of carbon dioxide (PaCO2) levels before and after 2 hours of NIV treatment were significantly decreased in both groups: from 61.9±23.8 mm Hg to 54.9±17.6 mm Hg in the control group (P<0.001) and from 54.9±15.1 mm Hg to 51.1±15.1 mm Hg in the sedation group (P=0.048). No significant differences were observed in the success rate of NIV weaning, complications, length of ICU stay, ICU survival rate, or hospital survival rate between the groups. In NIV patients, analgosedation therapy may have no harmful effects on complications, NIV weaning success, and mortality compared to the control group. Therefore, sedation during NIV may not be unsafe and can be used in patients for pain control when indicated.